2020
DOI: 10.1088/1757-899x/935/1/012019
|View full text |Cite
|
Sign up to set email alerts
|

Some properties of laminated veneer lumber manufactured from oil palm trunk

Abstract: Indonesia is the largest oil palm producer in the world and it was predicted that around 7 million metric tons was left in the field as a replanting waste, including palm frond and trunk. The utilization of this waste as a raw material of composite products may overcome the problem. The objective of this study was to determine the physical and mechanical properties of Laminated Veneer Lumber (LVL) made of oil palm trunk. Laboratory scale five-ply LVLs glued with urea formaldehyde adhesive were fabricated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Delamination in LVLs can be reduced by alternately replacing the lighter poplar and paulownia layers with denser hornbeam layers. Similar findings were reported by Sulastiningsih et al (2020), who indicated that density is the dominant parameter in determining the shrinkage behavior of wood, with denser wood generally experiencing more shrinkage from the green to oven-dry condition. Based on the results, it is recommended to enhance the physical and mechanical properties of LVL by replacing the layers of fast-growing species such as poplar and paulownia with denser wood like hornbeam in an alternating manner.…”
Section: Delamination and Swellingsupporting
confidence: 88%
See 1 more Smart Citation
“…Delamination in LVLs can be reduced by alternately replacing the lighter poplar and paulownia layers with denser hornbeam layers. Similar findings were reported by Sulastiningsih et al (2020), who indicated that density is the dominant parameter in determining the shrinkage behavior of wood, with denser wood generally experiencing more shrinkage from the green to oven-dry condition. Based on the results, it is recommended to enhance the physical and mechanical properties of LVL by replacing the layers of fast-growing species such as poplar and paulownia with denser wood like hornbeam in an alternating manner.…”
Section: Delamination and Swellingsupporting
confidence: 88%
“…They found that although the quality of eucalyptus veneer layers was not consistent, alternating lamination with poplar layers helped absorb the quality variations and improve the variation in the MOE. Sulastiningsih et al (2020) mentioned that incorporating jabon or mahoni wood veneers in oil palm LVL improved its physical and mechanical properties. When it comes to LVL used in exterior applications, a major concern is the risk of layers losing bond strength and delamination when exposed to atmospheric impacts and water absorption (Abd Malek et al 2019;Juciene et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…After conditioning for two weeks, the average equilibrium moisture content was 12.68%, 12.91% and 13.13% for rubberwood LVLs produced from 2-mm-thick veneer using 200, 240 and 280 g/m 2 glue spread rates, respectively. According to PRL-501 [26] and the Japanese Standard [27], the average moisture content of LVL intended for use in dry-service conditions should be less than 16% and 14%, respectively. The rubberwood LVL produced from this study meets the requirement of these standards.…”
Section: Moisture Content Density and Specific Gravitymentioning
confidence: 99%